Technology delivery system of the agricultural extension program at Cagayan State University - Raquepo, Marcelo R. (Education quarterly.)
This study was conducted to assess the technology delivery system of the agricultural extension program of the Cagayan State University. All of the extension workers, instructors and coordinators perceived the objectives of the agricultural extension program as clear, to much degree. Likewise, they considered the program objective favorably, to a much degree. They mentioned that the farmers were involved in planning the agricultural extension program, particularly on what activities to undertake. Generally, farmer program recipients adopted little of the knowledge acquired from the extension program. Eighty-four percent were still using the acquired knowledge skills.